2018
DOI: 10.1007/s11682-018-9879-z
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of associations between functional MRI activity and polygenic risk for schizophrenia and bipolar disorder

Abstract: Genetic factors account for up to 80% of the liability for schizophrenia (SCZ) and bipolar disorder (BD). Genome-wide association studies have successfully identified several genes associated with increased risk for both disorders. This has allowed researchers to model the aggregate effect of genes associated with disease status and create a polygenic risk score (PGRS) for each individual. The interest in imaging genetics using PGRS has grown in recent years, with several studies now published. We have conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 101 publications
2
28
0
Order By: Relevance
“…The high sMRI correlation between SCZ and BD is consistent with prior reports of sMRI similarities between the two disorders (26). Moreover, a large body of literature reports substantial etiologic overlap between the two disorders (27)(28)(29)(30)(31). Because of such data, the SCZ and BD have been described as sharing a continuum of etiology leading to psychotic (32), neurophysiological (32) and neurocognitive (33) symptoms.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The high sMRI correlation between SCZ and BD is consistent with prior reports of sMRI similarities between the two disorders (26). Moreover, a large body of literature reports substantial etiologic overlap between the two disorders (27)(28)(29)(30)(31). Because of such data, the SCZ and BD have been described as sharing a continuum of etiology leading to psychotic (32), neurophysiological (32) and neurocognitive (33) symptoms.…”
Section: Discussionsupporting
confidence: 84%
“…The ENPACT study (33) showed shared fronto-temporo-occipital grey matter volume deficits in the right hemisphere of two disorders. A systematic review of associations between functional MRI activity and polygenic risk for SCZ and BD (27) reported that genetic load for these disorders affects taskrelated recruitment of predominantly frontal lobe brain regions.…”
Section: Discussionmentioning
confidence: 99%
“…As the knowledge and evidence of imaging genetics increases, more nuanced structural and functional brain measures are being studied. For example, measures of brain connectivity and of task-dependent recruitment of multiple brain regions may be associated with genetic variation in psychosis ( Ranlund et al, 2017 ; Dezhina et al, 2019 ; Cao et al, 2020 ). Added to this, advanced methodological approaches integrating environmental exposures, gene-gene interactions, and epigenetics from a variety of ancestral cohorts, are needed to fully appreciate missing heritability ( Mufford et al, 2017 ; Alnæs et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Atypical brain activity findings have been reported for both schizophrenia [28][29][30] and major depressive disorder [31][32][33]. Interestingly, some similarities have been identified between schizophrenia-and major depressive disorder-related brain alteration patterns, particularly in regional homogeneity (ReHo) data, which represent local temporal homogeneity of regional blood oxygen level-dependent signals and can be used to assess resting-state neural activity [34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%